EVALUATING THE EFFECTIVENESS OF FORENSIC ACCOUNTING COMPETENCIES IN COMBATING PUBLIC SECTOR FRAUD IN MINISTRY OF FINANCE IN NORTHWESTERN NIGERIA - Sulaimam Sabo; Prof MUSA Farouk Adeiza; Ibrahim Halidu Saidu; Abdullahi Ya'u Usman (Gusau Journal of Accounting and Finance)
This study examines the effectiveness of forensic accounting competencies, such as communication skills, technological skills, accounting and auditing skills, and auditor’s self-efficacy, in combating fraud in finance ministries in Northwestern Nigeria. The primary objective is to evaluate how these competencies skills contribute to enhancing fraud detection and prevention in the public sector. Primary data were collected through structured questionnaires distributed to employees in finance ministries, including auditors, accountants, and forensic experts. The data were analyzed using regression techniques, allowing for an in-depth examination of the relationships between the dependent variable (fraud management) and the independent variables. The findings reveal that communication skills, technological skills, and accounting and auditing skills have significant positive effects on fraud management, while auditor’s self-efficacy shows a positive but statistically insignificant relationship. These results underscore the importance of technical and behavioral fraud detection and Prevention competencies in addressing fraud challenges in the public sector. Based on the findings, the study recommends targeted training programs to enhance communication and technical skills, investments in advanced forensic tools, and the implementation of mentoring programs to build confidence among auditors. These measures are essential for strengthening fraud management frameworks and improving public sector accountability and transparency.